Get Shorty [videorecording (DVD)] - Sonnenfeld, Barry; DeVito, Danny; Travolta, John, 1954-; Hackman, Gene; Russo, Rene; Leonard, Elmore, 1925-2013 (MGM Home Entertainment, 1998)
Loanshark Chili Palmer has done his time as a gangster, so when "business" takes him to Los Angeles to collect a debt from down and out filmmaker Harry Zimm, he talks tough and then pitches Harry a script idea. Everything would be smooth for this cool new producer, if it weren't for the drug smugglers and gangsters who won't leave him alone.